(untitled) (American Journal of Medical Science and Innovation, 2023)
Entamoeba histolytica is an extraintestinal protozoa that is feco-orally transmitted and exists as cysts or trophozoites, which may cause either asymptomatic infection or invasive intestinal and extraintestinal disease, respectively. Most infections (amoebiasis) are found in communities with poor environmental sanitation and unhygienic water and food handling practices. Recurrent symptomatic intestinal amoebiasis is associated with significant personal and public health cost implications and warrants a deliberate and thorough search for a source of the feco-oral transmission. In this study, we present a case of a woman with recurrent symptomatic amoebiasis to underscore the importance of a detailed social history in establishing source control in the case management of amoebiasis.